La delimitación como forma de protección de los páramos en Colombia y el principio de precaución : retos y limitaciones (2017)
This research project aims, through the study of different judicial pronunciations of the Constitutional Court of Colombia and of the administrative court, specialized journals and empirical approaches, to study the precautionary principle as a fundamental element regarding the protection of the ecosystem of Paramos in Colombia ithrough its delimitation. This, with the purpose of evaluating the dynamics for its implementation in the national territory and establishing the shortcomings in its use. The current situation of vulnerability of the enviroment experienced not only by Colombia but the entire world, is a clear example of the need for research in relation to the proposed topic. Also, the research problem has as background different national judicial decitions, pronouncements of the international and national institutions or authorities in relation to the function of the precautionary principle and its articulation in the Colombian legal order, specifically with regard to the delimitation of the ecosystems of páramos...